Quaternary Lidocaine Derivative QX-314 Activates and Permeates Human TRPV1 and TRPA1 to Produce Inhibition of Sodium Channels and Cytotoxicity - Stueber, Thomas; Eberhardt, Mirjam J.; Hadamitzky, Christoph; Jangra, Annette; Schenk, Stefan; Dick, Felicia; Stoetzer, Carsten; Kistner, Katrin; Reeh, Peter; Binshtok, Alexander M.; Leffler, Andreas (Anesthesiology, 2016)
BACKGROUND: The relatively membrane-impermeable lidocaine derivative QX-314 has been reported to permeate the ion channels transient receptor potential vanilloid 1 (TRPV1) and transient receptor potential cation channel, subfamily A, member 1 (TRPA1) to induce a selective inhibition of sensory neurons. This approach is effective in rodents, but it also seems to be associated with neurotoxicity. The authors examined whether the human isoforms of TRPV1 and TRPA1 allow intracellular entry of QX-314 to mediate sodium channel inhibition and cytotoxicity. METHODS: Human embryonic kidney 293 (HEK-293) cells expressing wild-type or mutant human (h) TRPV1 or TRPA1 constructs as well as the sodium channel Nav1.7 were investigated by means of patch clamp and ratiometric calcium imaging. Cytotoxicity was examined by flow cytometry. RESULTS: Activation of hTRPA1 by carvacrol and hTRPV1 by capsaicin produced a QX-314-independent reduction of sodium current amplitudes. However, permeation of QX-314 through hTRPV1 or hTRPA1 was evident by a concentration-dependent, use-dependent inhibition of Nav1.7 activated at 10 Hz. Five and 30 mM QX-314 activated hTRPV1 via mechanisms involving the intracellular vanilloid-binding domain and hTRPA1 via unknown mechanisms independent of intracellular cysteins. Expression of hTRPV1, but not hTRPA1, was associated with a QX-314-induced cytotoxicity (viable cells 48 ± 5% after 30 mM QX-314) that was ameliorated by the TRPV1 antagonist 4-(3-chloro-2-pyridinyl)-N-[4-(1,1-dimethylethyl)phenyl]-1-piperazinecarboxamide (viable cells 81 ± 5%). CONCLUSIONS: The study data demonstrate that QX-314 directly activates and permeates the human isoforms of TRPV1 and TRPA1 to induce inhibition of sodium channels, but also a TRPV1-dependent cytotoxicity. These results warrant further validation of this approach in more intact preparations and may be valuable for the development of this concept into clinical practice.
EVALuna2:32812